Zoonotic foodborne diseases in a tertiary healthcare setting: diagnostics, resistance and underreporting of salmonellosis in Northern Portugal. (March 2022) - Rocha, R.; Matos, M.I.; Pinto, J.; Sarmento, A.
Abstract : Purpose: Salmonellosis and campylobacteriosis are the two most common zoonotic foodborne diseases. In Europe, although incidence rates seem to be stable in the last five years, growing antimicrobial resistance is concerning. In Portugal, although reporting of these diseases is mandatory, it is estimated that a significant percentage of cases diagnosed in tertiary healthcare is not reported. The aim of this study is to describe the nature of Salmonella isolated in our hospital, focusing on resistance trends, and to determine rates of underreporting. Methods & Materials: We reviewed the Salmonella sp. identified at the microbiology laboratory of the São João University Hospital by isolation in culture or PCR amplification, from patients presenting with symptoms at the emergency department or out-patient setting. The study was conducted between 2010 and 2020. Results: Between 2010 and 2020, 445 Salmonella sp. isolates were identified. 53.0% of patients were male and median age was 9 (approximately 50% under 10). 76.2% of isolations were from fecal samples, 11.0% from blood and 8.8% from urine, mostly by culture (99.3%). Most products were collected in the pediatrics emergency (42.0%), adult emergency (17.5%) and adult ward (11.9%). The most commonly identified serogroups were S. Typhimurium (60.4%) and S. Enteritidis (19.8%). In the 428 isolates with available antimicrobial susceptibility testing, the following resistance rates were observed: ciprofloxacin 69.3%, ampicillin 63.8%, gentamicin 53.0%, amikacin 48.5%, co-trimoxazole 11.7%, cefotaxime 1.7%, ceftazidime 1.4%, meropenem and ertapenem 0%. Resistance to colistin was detected in 2 cases. Resistance to ciprofloxacin increased significantly during the years of this study, while aminoglycoside resistance decreased and resistance profile for the remaining antibiotics did not show significant difference. Only 33% of cases were notified to the National Monitoring System between 2016 and 2019. Conclusion: Our study underlines the burden of salmonellosis in children under 5 years old. S. Typhimurium was the most frequent serogroup identified, as expected by the results of similar studies. A significant resistance to fluoroquinolones was observed in our setting, with rising trends. Underreporting, even in hospital settings, may deter efforts to control the emergence of these pathogens and their increasing resistance to first line antibiotics.